Implementing sequentially consistent shared objects using broadcast and point-to-point communication. - Fekete, Alan (Journal of the ACM)
This paper presents and proves correct a distributed algorithm that implements a sequentially consistent collection of shared read/update objects. This algorithm is a generalization of one used in the Orca shared object system. The algorithm caches objects in the local memory of processors according to application needs; each read operation accesses a single copy of the object, while each update accesses all copies. The algorithm uses broadcast communication when it sends messages to replicated copies of an object, and it uses point-to-point communication when a message is sent to a single copy, and when a reply is returned. Copies of all objects are kept consistent using a strategy based on sequence numbers for broadcasts.The algorithm is presented in two layers. The lower layer uses the given broadcast and point-to-point communication services, plus sequence numbers, to provide a new communication service called a context multicast channel. The higher layer uses a context multicast channel to manage the object replication in a consistent fashion. Both layers and their combination are described and verified formally, using the I/O automation model for asynchronous concurrent systems.